Assessment of health status in adolescents with spina bifida in the West Bank, Palestine: sense of coherence and self-perceived health. Issue 19 (11th September 2022) - Nahal, Maha Sudki Hmeidan; Wigert, Helena; Imam, Asma; Axelsson, Åsa B.
Abstract: Purpose: To assess self-perceived health and sense of coherence (SOC) in adolescents with spina bifida (SB) in the West Bank, Palestine, compared to a healthy reference group. Further, to assess the association between impairment levels in the adolescents with SB and their self-perceived health and SOC. Methods: Fifty adolescents with SB and 150 healthy adolescents completed measures of self-perceived health – the Pediatric Quality of Life Inventory (PedsQL TM 4.0) – and SOC. The rehabilitation center nurses identified the physical impairments of the adolescents with SB from their medical records, and classified them by impairment severity. Results: Adolescents with SB reported lower self-perceived health (PedsQL median 55, IQR 42–67), than the reference group (median 85, IQR 74–90), p < 0.001, and lower SOC (median 47, IQR 44–50) than the reference group (median 55, IQR 44–61), p < 0.001. Impairment level was inversely associated with both self-perceived health and SOC. Conclusions: The low self-perceived health and SOC among adolescents with SB in Palestine indicate the need for collaboration between policy makers and providers to improve these adolescents' physical and social environment and to promote the rehabilitation services provided for them. Implications for rehabilitation: The low self-perceived health and SOC among adolescents with SB in Palestine highlight the need to develop appropriate interventions to promote their health, independency, and self-care management. Collaboration of the caregivers and health care providers is required to develop, implement, and evaluate intervention programs that might promote coping abilities of the adolescents with SB. A multidisciplinary approach is needed to set goals that have a meaningful impact on social, emotional, behavioral, and educational conditions of the adolescents with SB and in different settings, for example, home, school, and community. The environment in Palestine presents barriers to the social engagement of adolescents with SB, and new ways are needed to enhance their participation in the society to promote their self-concept and wellbeing.